Expectations, frames and practices of genetic counselling in different contexts of genetic testing - Rantanen, Elina (Annales Universitatis Turkuensis D 1130, 2014)
Genetic counselling is a process in which the counsellee receives information and support concerning a genetic disease. This study examines the genetic counselling attached to genetic testing. Since genetic information is increasing alongside new testing technologies and the situations faced at the genetic clinics will therefore be more diverse, it is essential to assess what the expectations directed at genetic counselling are. It is also important to compare how they face the current counselling practices. In this study, the expectations, frames and practices of genetic counselling in different contexts of genetic testing were examined from three different perspectives: First, international guidelines covering genetic counselling were analysed to summarise what is expected from genetic counselling and to study how genetic information is framed. Second, national experts in European countries were asked about the regulations and practices of genetic counselling in their country. Finally, ten counsellees who had visited a genetic clinic were interviewed to analyse their expectations and experiences. The counsellees’ perspective was also approached through the background review of the previous studies on counsellees’ experiences. On the basis of the study, there are basic elements that are expected to be covered in genetic counselling from all perspectives. However, the views concerning bioethics, genetic exceptionalism and psychosocial aspects vary depending on the perspective and on the individual situation. Since there are sometimes more differences than similarities between genetic tests, no universal recommendations for counselling can be applied. The practices of genetic counselling should be defined situationally, emphasising the individual needs over the genes.

Tässä työssä käsitellään geenitestauksen yhteydessä tapahtuvaa perinnöllisyysneuvonta, jossa neuvottava saa tietoa ja tukea geneettiseen sairauteen tai vammaan liittyen. Testausteknologioiden kehittyessä geneettinen tieto lisääntyy ja perinnöllisyysklinikoilla kohdattavat tilanteet moninaistuvat. Siksi on tärkeää arvioida, minkälaisia perinnöllisyysneuvontaan kohdistuvat odotukset ovat ja miten ne vastaavat perinnöllisyysneuvonnan nykyisiä käytäntöjä. Tässä tutkimuksessa tarkasteltiin perinnöllisyysneuvontaan kohdistettavia odotuksia sekä sen kehyksiä ja käytäntöjä kolmesta eri näkökulmasta. Perinnöllisyysneuvontaa käsittelevien kansainvälisten ohjeistojen analyysilla selvitettiin, mitä ideaalilta perinnöllisyysneuvonnalta odotetaan ja miten geneettistä tietoa kehystetään. Kansallisilta asiantuntijoilta kysyttiin Euroopan maiden perinnöllisyysneuvontaan liittyvästä lainsäädännöstä ja käytännöistä. Lopuksi kymmentä perinnöllisyysneuvonnassa käynyttä neuvottavaa haastateltiin heidän odotuksistaan ja kokemuksistaan. Neuvottavien näkökulmaa tarkasteltiin lisäksi aiempien neuvottavien kokemuksia käsittelevien tutkimusten tausta-analyysilla. Tutkimuksen perusteella perinnöllisyysneuvonnalta odotetaan tiettyjä peruselementtejä kaikista näkökulmista tarkasteltuna. Bioetiikkaa, geneettistä ekseptionalismia ja psykososiaalisia tekijöitä koskevat näkemykset kuitenkin vaihtelevat riippuen perspektiivistä ja yksittäisestä tilanteesta. Koska geenitestien välillä on toisinaan enemmän eroavaisuuksia kuin yhtäläisyyksiä, universaaleja suosituksia ei kannata soveltaa kaikessa neuvonnassa. Perinnöllisyysneuvonnan käytännöt pitäisi määritellä tilanteisesti ja perustella geenien sijaan yksilöllisillä tarpeilla.